The role of natural products and traditional Chinese medicine formulas in postpartum depression: mechanism and prospects - Shang, Ruirui; Lu, Yitong; Gao, Haonan; Zhong, Xia; Yu, Xiaowen; Li, Guoqiang (Frontiers in Pharmacology, 2025)
Postpartum depression (PPD) is a common postpartum complication mediated by multiple factors, which can lead to dual damage to both maternal and infant health. There is an urgent need to explore alternative intervention strategies, as the current conventional antidepressant medications have drawbacks, including delayed onset, severe side effects, and low patient tolerance. Due to their multi-target potential, certain metabolites derived from traditional Chinese medicine (TCM) and other natural products are being investigated as treatments for PPD. However, a systematic understanding of their molecular mechanisms, grounded in the pathophysiology of PPD, is lacking. Therefore, this article synthesizes recent literature to systematically review the pathophysiological mechanisms of PPD and to elucidate the molecular mechanisms underlying the therapeutic effects of TCM formulas and natural products. This review also critically discusses the limitations of current research—particularly issues related to standardization and safety—and proposes key priorities for future preclinical studies and clinical translation.